Hubungan Kecerdasan Emosional dengan Bullying Victimization pada Mahasiswa Ilmu Kesehatan di Sumatera Barat - Asri Rima Oktavia; Maya Yasmin (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
This study aims to determine the relationship between emotional intelligence and bullying victimization in health science students in West Sumatra. The study used a quantitative method on 383 health science students in West Sumatra. The instrument in this study was made by the researcher himself, where the emotional intelligence scale refers to the theory put forward by Mayer (2004) and the bullying victimization scale refers to the theory of Smith et al. (1999). The results of the study showed that there was a significant negative relationship between emotional intelligence and bullying victimization (r = -0.154, p <0.05). The results of this study indicate that the higher the level of emotional intelligence, the lower the bullying victimization experienced by health science students in West Sumatra. Conversely, a low level of emotional intelligence can increase the possibility of becoming a victim of bullying in health science students in West Sumatra.